A Comprehensive Study on the Assessment of CaCO3-, Nano-CaCO3-, and Glass Fiber Chopped Strand (GFCS)-Treated Clay in Terms of Bearing Capacity and Settlement Enhancements - Baki Bağrıaçık; Barış Mahmutluoğlu; Abdulkadir Ürünveren (Applied Sciences)
Nanomaterials have been one of the latest trends used by geotechnical engineers for improving insufficient soil criteria. This study aims to assess the usability of CaCO3, nano-CaCO3 and Glass Fiber Chopped Strands (GFCSs) in the improvement procedures for clay soil media by performing traditional and laboratory model experiments. Clay samples mixed with CaCO3 at 5%, nano-CaCO3 at 0.75% and GFCSs at 2.0% separately provided 1.49, 1.68 and 1.86 times increments in the bearing capacity values in comparison with plain clay, respectively. Mixtures of clay, GFCSs at 1.5% and nano-CaCO3 at 0.75% enabled the most optimal result of 2.58 times improved bearing capacities. Curing durations had a significant effect on increasing the bonding between nano-CaCO3 and clay which led to further improved conditions. Settlement enhancements of up to 6.80% were recorded for the mixtures of nano-CaCO3, GFCSs and clay as well. Thus, improvements were reached in terms of bearing capacity and settlements along with the applicability and economy of the related procedures, of which the details can be seen in the following sections of this study.